CT of neonatal herpes encephalitis. - Herman, T E; Cleveland, R H; Kushner, D C; Taveras, J M (American Journal of Neuroradiology, 1985)
Seven neonates with proven herpes (HSV type 2) encephalitis exhibited a characteristic sequence of findings on cranial computed tomography (CT). The initial CT abnormalities in all infants were fingerlike areas of cortical increased attenuation noted on unenhanced scans obtained 2-30 days after presentation. These usually were accentuated by increased white-matter lucency. Subsequently (more than 30 days after presentation), extensive cerebral destruction, multicystic encephalomalacia, and calcification were seen on follow-up CT scans obtained in five infants.